Evolution of Alternative Splicing in Eudicots - Ling, Zhihao; Brockmöller, Thomas; Baldwin, Ian T.; Xu, Shuqing (Frontiers in Plant Science, 2019)
Alternative pre-mRNA splicing (AS) is prevalent in plants and is involved in many interactions between plants and environmental stresses. However, the patterns and underlying mechanisms of AS evolution in plants remain unclear. By analyzing the transcriptomes of four eudicot species and three Brassicaceae species, we revealed that AS diverged even among closely related species, largely due to the gains and losses of AS events among orthologous genes. Furthermore, based on a subset of AS, in which AS can be directly associated with specific transcripts, we found that AS that generates transcripts containing premature termination codons (PTC), are likely more conserved than those that generate non-PTC containing transcripts. This suggests that AS coupled with nonsense-mediated decay (NMD) might play an important role in affecting mRNA levels post-transcriptionally. To understand the mechanisms underlying the divergence of AS, we analyzed the key determinants of AS using a machine learning approach. We found that the presence/absence of alternative splice site (SS) within the junction, the distance between the authentic SS and the nearest alternative SS, the size of exon-exon junctions were the major determinants for both alternative 5’ donor site and 3’acceptor site among the studied species, suggesting a relatively conserved AS mechanism. The comparative analysis further demonstrated that variations of the identified AS determinants significantly contributed to the AS divergence among closely related species in both Solanaceae and Brassicaceae taxa. Together, these results provide detailed insights into the evolution of AS in plants.